Local Government Supervision of the Circulation of Tuak (Alcoholic) Beverages in the Context of Implementing Public Order, Peace and Community Protection - Muhamad Haiqal Hakiki; Emilda Firdaus; Separen Separen (PATTIMURA Legal Journal, 2025)
Introduction: The circulation of alcoholic beverages in Tembilahan District is a social problem that requires strict supervision from the local government. Based on the Regional Regulation of Indragiri Hilir Regency Number 3 of 2023, supervision of the circulation of alcoholic beverages is the responsibility of the Pamong Praja Police Unit to maintain public order, peace, and community protection. Purposes of the Research: The purpose of this study is to find out the Regional Government's supervision of the circulation of alcoholic beverages in Tembilahan District, to find out the inhibiting factors in the supervision, and the efforts made by the Regional Government in this regard. Methods of the Research: The type of research carried out is sociological legal research conducted in the Regional Government of Indragiri Hilir Regency. The data sources used are primary data and secondary data. The data collection techniques used were interviews, and literature reviews. The data is then analyzed which is qualitative and then concluded using a deductive thinking method. Results Main Findings of the Research: The result of this study is that the supervision of the circulation of alcoholic beverages by the Pamong Praja Police Unit is still not optimal, as seen from the low intensity of raids and the lack of strict action against violators. The main inhibiting factors in this supervision include limited facilities and infrastructure, information leakage, and lack of community participation. To overcome this obstacle, the local government plans to increase monitoring facilities and facilities and the use of technology such as Closed-Circuit Television in areas prone to alcohol trafficking. The establishment of a Rapid Reaction Unit involving the Pamong Praja Police Unit, the police, and the community is expected to strengthen supervision and increase the effectiveness of local law enforcement.